EDIBLE FILM FOR FOOD PACKAGING - Hakimah Nurjanah; Hilman Imadul Umam; Teguh Pambudi (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
The purpose of this review article is to provide information about edible film, materials used, manufacturing methods, application for food packaging, and opportunities for future benefits of edible film. The method used by the author in reviewing this article, is by reading various journals from other authors and write the conclude using author own language. The conclusion is, edible film has potential to replace plastics (synthetic polymers) as food packaging. The ingredients used for edible film production are hydrocolloid (protein, polysaccharides, and alginates), lipid (polysaccharides, and alginates) and composite (mix of hydrocolloid and lipid). The methods for edible film production are wet process and dry process. Edible film can be used as food packaging, including cheese, meat, fish, vegetables, and fruit. Prospect of edible film has the potential to increase in the future because people are realizing the importance of reducing food waste with ecofriendly material as food packaging.